Characterization of transgenic potato (Solanum tuberosum) tubers with increased ADPglucose pyrophosphorylase. - Sweetlove, L; Burrell, M; ap Rees, T (1996)
The aim of the work described in this paper was to characterize the tubers of potato (Solanum tuberosum var. Prairie) plants that had been transformed with the Escherichia coli ADPglucose pyrophosphorylase (EC 2.7.7.27) gene, glgC-16, under the control of a patatin promoter. Over 30 lines of transformed plants with increased ADPglucose pyrophosphorylase activity were obtained. The tubers of six of these lines were compared with those of control plants expressing the gene for beta-glucuronidase. The average increase in pyrophosphorylase activity was 200%, and the highest was 400%. Western immunoblotting of tuber extracts showed that the amounts of glgC-16 protein were linearly related to the extractable activity of the ADPglucose pyrophosphorylase. Cell fractionation studies showed that the increased activity of the pyrophosphorylase in the glgC-16 tubers had a similar intracellular location, the amyloplast fraction, to that found in the control tubers. No pleiotropic changes in the maximum catalytic activities of the following enzymes could be detected in the glgC-16 tubers: sucrose synthase, fructokinase, UDPglucose pyrophosphorylase, phosphofructokinase, soluble starch synthase, starch branching enzyme, phosphoglucomutase and alkaline inorganic pyrophosphatase. The glgC-16 tubers are held to be suitable for the study of the role of ADPglucose pyrophosphorylase in the control of starch synthesis.